A second tubulin binding site on the kinesin-13 motor head domain is important during mitosis. - Dong Zhang (Public Library of Science (PLoS), 2013)
Kinesin-13s are microtubule (MT) depolymerases different from most other kinesins that move along MTs. Like other kinesins, they have a motor or head domain (HD) containing a tubulin and an ATP binding site. Interestingly, kinesin-13s have an additional binding site (Kin-Tub-2) on the opposite side of the HD that contains several family conserved positively charged residues. The role of this site in kinesin-13 function is not clear. To address this issue, we investigated the in-vitro and in-vivo effects of mutating Kin-Tub-2 family conserved residues on the Drosophila melanogaster kinesin-13, KLP10A. We show that the Kin-Tub-2 site enhances tubulin cross-linking and MT bundling properties of KLP10A in-vitro. Disruption of the Kin-Tub-2 site, despite not having a deleterious effect on MT depolymerization, results in abnormal mitotic spindles and lagging chromosomes during mitosis in Drosophila S2 cells. The results suggest that the additional Kin-Tub-2 tubulin biding site plays a direct MT attachment role in-vivo.